2014
DOI: 10.1042/bj20131673
|View full text |Cite
|
Sign up to set email alerts
|

A small-molecule benzimidazole derivative that potently activates AMPK to increase glucose transport in skeletal muscle: comparison with effects of contraction and other AMPK activators

Abstract: AMPK (AMP-activated protein kinase) is an attractive therapeutic drug target for treating metabolic disorders. We studied the effects of an AMPK activator developed by Merck (ex229 from patent application WO2010036613), comparing chemical activation with contraction in intact incubated skeletal muscles. We also compared effects of ex229 with those of the Abbott A769662 compound and AICAR (5-amino-4-imidazolecarboxamide riboside). In rat epitrochlearis muscle, ex229 dose-dependently increased AMPK activity of α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 49 publications
2
73
0
Order By: Relevance
“…This is an important consideration because previous studies using A769662, the first direct small molecule AMPK activator to be described [3], led to the suggestion that only b1-containing complexes are targets for activation [43]. With the identification of more potent AMPK activators it is now clear that this is not the case [44]. However, the finding that drugs have different binding affinities between b1 and b2 complexes opens up the possibility of designing isoform-selective AMPK activators.…”
Section: Pharmacological Ampk Activatorsmentioning
confidence: 80%
“…This is an important consideration because previous studies using A769662, the first direct small molecule AMPK activator to be described [3], led to the suggestion that only b1-containing complexes are targets for activation [43]. With the identification of more potent AMPK activators it is now clear that this is not the case [44]. However, the finding that drugs have different binding affinities between b1 and b2 complexes opens up the possibility of designing isoform-selective AMPK activators.…”
Section: Pharmacological Ampk Activatorsmentioning
confidence: 80%
“…The β-subunit contains a conserved glycogen-binding domain called the carbohydrate-binding module (CBM), forming an interface between the α-and γ-subunits. High glycogen levels, particularly in muscle, antagonize AMPK activation (McBride and Hardie 2009;Lai et al 2014). Interestingly, the CBM can be recognized in the AMPKβ subunit sequences of protists, such as Giardia lamblia.…”
Section: Regulation Of Ampkmentioning
confidence: 97%
“…At a much higher concentration (2 mM), A769662 stimulated glucose uptake; however, it was mediated through an AMPK-independent/phosphoinositide 3-kinase-dependent mechanism due to unknown off-target effect(s) (43). Another small-molecule AMPK activator, 991 [also known as ex229 (22)], has recently been described. Structural studies have shown that 991 binds to a site formed between the small lobe of the α-subunit kinase domain and the β-subunit carbohydrate-binding module (4, 46), which is also the binding site for A769662, termed the allosteric drug and metabolite-binding site (ADaM) (23).…”
mentioning
confidence: 99%
“…Structural studies have shown that 991 binds to a site formed between the small lobe of the α-subunit kinase domain and the β-subunit carbohydrate-binding module (4, 46), which is also the binding site for A769662, termed the allosteric drug and metabolite-binding site (ADaM) (23). 991 is 5- to 10-fold more potent than A769662 in cell-free assays (46) and has been shown to stimulate AMPK activity of both β1- and β2-containing complexes and to increase glucose transport in isolated mouse skeletal muscle ex vivo (22). …”
mentioning
confidence: 99%